2018
DOI: 10.1002/jcp.27482
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0136666 promotes the proliferation and invasion of colorectal cancer through miR‐136/SH2B1 axis

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer-related death worldwide. Currently, an increasing evidence showed that circular RNAs (circRNAs) play important roles in tumor progression. However, the effects and underlying mechanisms of circRNAs in CRC progression remain unclear. In the present study, through circRNA high-throughput sequencing and quantitative real-time polymerase chain reaction, we identified that hsa_circ_0136666 was significantly overexpressed in CRC tissues and cell lines. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 29 publications
(41 reference statements)
5
65
0
Order By: Relevance
“…CircRNAs play an important regulatory role in the occurrence and progression of diseases, especially in cancers. They are expected to become novel tumor biomarkers of diagnosis and new targets for treatment of gastric cancer, hepatocellular carcinoma, colorectal cancer, lung cancer, breast cancer, bladder cancer, and esophageal squamous cell carcinoma …”
Section: The Potential Diagnostic Roles Of Circrnas In Cancersmentioning
confidence: 99%
“…CircRNAs play an important regulatory role in the occurrence and progression of diseases, especially in cancers. They are expected to become novel tumor biomarkers of diagnosis and new targets for treatment of gastric cancer, hepatocellular carcinoma, colorectal cancer, lung cancer, breast cancer, bladder cancer, and esophageal squamous cell carcinoma …”
Section: The Potential Diagnostic Roles Of Circrnas In Cancersmentioning
confidence: 99%
“…14 For example, a recent study indicated that hsa_-circ_0136666 upregulates SH2B1 expression to facilitate colorectal cancer cell progression via sponging miR-136. 15 In BC, Xu et al, 16 uncovered that overexpressed circRNA circ_0005230 increases CBX8 expression via interacting with miR-618 to promote BC cell progression. However, the research regarding circRNAs in BC is just beginning.…”
Section: Introductionmentioning
confidence: 99%
“…Then, 27 articles were excluded for the following reasons: 5 were not about circRNAs or CRC, 10 did not report relevant outcomes, 3 were review articles, 1 was animal data, and 8 had insufficient data. In summary, there were 19 studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] included in this study, with a total of 1307 patients, including 11 on clinical parameters, 8 on prognosis and 7 on diagnosis.…”
Section: Search Resultsmentioning
confidence: 99%